Venus and Mercury, and How to Observe Them - Grego, Peter (Springer, 2017)
Venus and Mercury have long been regarded as difficult targets for amateur observers, but advances in commercially-made telescopes have brought them within the skills of observers of only moderate experience. Peter Grego’s fascinating book presents an up-to-date, detailed description of the history and geology of the so-called inferior planets, and provides the latest, most useful advice on observing and recording them with commercially-available telescopes and cameras. The book also offers a wealth of detailed practical information on every aspect of observing, from safely targeting the two planets, through visual observing, to sketching and electronic imaging.